Genomic Insertion of a Heterologous Acetyltransferase Generates a New Lipopolysaccharide Antigenic Structure in Brucella abortus and Brucella melitensis - Martínez-Gómez, Estrella; Ståhle, Jonas; Gil-Ramírez, Yolanda; Zúñiga-Ripa, Amaia; Zaccheus, Mona; Moriyón, Ignacio; Iriarte, Maite; Widmalm, Göran; Conde-Álvarez, Raquel (Frontiers in Microbiology, 2018)
Brucellosis is a bacterial zoonosis of worldwide distribution caused by bacteria of the genus Brucella. In B. abortus and B. melitensis, the major species infecting domestic ruminants, the smooth lipopolysaccharide (S-LPS) is a virulence factor. This S-LPS carries a N-formyl-perosamine homopolymer O-polysaccharide that is the major antigen in serodiagnostic tests and is required for virulence. We report that the Brucella O-PS can be structurally and antigenically modified using wbdR, the acetyl-transferase gene involved in N-acetyl-perosamine synthesis in Escherichia coli O157:H7. Brucella constructs carrying plasmidic wbdR expressed a modified O-polysaccharide but were unstable, a problem circumvented by inserting wbdR into a neutral site of chromosome II. As compared to wild-type bacteria, both kinds of wbdR constructs expressed shorter O-polysaccharides and NMR analyses showed that they contained both N-formyl and N-acetyl-perosamine. Moreover, deletion of the Brucella formyltransferase gene wbkC in wbdR constructs generated bacteria producing only N-acetyl-perosamine homopolymers, proving that wbdR can replace for wbkC. Absorption experiments with immune sera revealed that the wbdR constructs triggered antibodies to new immunogenic epitope(s) and the use of monoclonal antibodies proved that B. abortus and B. melitensis wbdR constructs respectively lacked the A or M epitopes, and the absence of the C epitope in both backgrounds. The wbdR constructs showed resistance to polycations similar to that of the wild-type strains but displayed increased sensitivity to normal serum similar to that of a per R mutant. In mice, the wbdR constructs produced chronic infections and triggered antibody responses that can be differentiated from those evoked by the wild-type strain in S-LPS ELISAs. These results open the possibilities of developing brucellosis vaccines that are both antigenically tagged and lack the diagnostic epitopes of virulent field strains, thereby solving the diagnostic interference created by current vaccines against Brucella.